2022
DOI: 10.1186/s41182-022-00471-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study of medicinal plants utilized in the management of candidiasis in Northern Uganda

Abstract: Background The emergence of resistant Candida species to antifungal drugs has led to resurgence in herbal usage globally. However, little is known about anti-candida plants. This study explored ethnomedicinal plants as treatment option for candidiasis in Pader, Northern Uganda. Methods A cross-sectional survey of potential anti-candida plants was conducted using questionnaires, focus group discussions and field observations in March 2022. Sixty-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 81 publications
2
6
0
Order By: Relevance
“…Other plant species that were most frequently mentioned include L. nepetifolia (Lamiaceae), C. macrostachyus (Euphorbiaceae) and R. tridentata (Vitaceae) ( Table 1 ). Most of the mentioned plant species were trees whereby, roots were the plant parts mostly harvested for preparation of herbal medicines and the majority of the plants were collected from the wild ( Table 1 ), which is consistent with the previous findings [ [40] , [41] , [42] ]. In this study, the calculated informant consensus factor (ICF) was 0.47 implying that the TMPs use different medicinal plants to manage HIV/AIDS.…”
Section: Resultssupporting
confidence: 90%
“…Other plant species that were most frequently mentioned include L. nepetifolia (Lamiaceae), C. macrostachyus (Euphorbiaceae) and R. tridentata (Vitaceae) ( Table 1 ). Most of the mentioned plant species were trees whereby, roots were the plant parts mostly harvested for preparation of herbal medicines and the majority of the plants were collected from the wild ( Table 1 ), which is consistent with the previous findings [ [40] , [41] , [42] ]. In this study, the calculated informant consensus factor (ICF) was 0.47 implying that the TMPs use different medicinal plants to manage HIV/AIDS.…”
Section: Resultssupporting
confidence: 90%
“…The enzyme encoded by this gene, 14-alpha demethylase of lanosterol, will have a lower affinity for the drug; in turn, the CDR (an ABC transporter) and MDR genes (a major facilitator) are overexpressed, resulting in reduced accumulation of the drug in the fungal cell [68]. A study based in Africa have shown that herbalists use different methods and agree on high efficacy [69]. They have identified some 32 plant species with antifungal activity, of which 43.8% are herbs, including Momordica foetida, Sansevieria dawei, and Clerodendrum umbellatum [69].…”
Section: Herbal Preparations Used To Treat the Vagina And Vulvamentioning
confidence: 99%
“…A study based in Africa have shown that herbalists use different methods and agree on high efficacy [69]. They have identified some 32 plant species with antifungal activity, of which 43.8% are herbs, including Momordica foetida, Sansevieria dawei, and Clerodendrum umbellatum [69]. Many of the herbs used in Uganda have not been described by the specialized literature, but Momordica foetida has been shown to contain alkaloids, flavonoids, and phenolic glycosides with potential medicinal properties [69].…”
Section: Herbal Preparations Used To Treat the Vagina And Vulvamentioning
confidence: 99%
See 2 more Smart Citations